The ubiquitin-activating enzyme E1 as a novel therapeutic target for the treatment of restenosis. (April 2016) - Qin, Zhexue; Cui, Bin; Jin, Jun; Song, Mingbao; Zhou, Baoshang; Guo, Hongfeng; Qian, Dehui; He, Yongming; Huang, Lan
Abstract: Aims: The ubiquitin-activating enzyme E1 (UBA1, E1), the apex of the ubiquitin proteasome pathway, plays a critical role in protein degradation and in pathological processes. Whether UBA1 participates the development of vascular restenosis remains unknown. This study aims to determine the role of UBA1 in the development of balloon injury induced neointimal formation. Methods and results: Immunostaining and western blots were used to examine the expression of the ubiquitinated protein in the injured carotid after angioplasty. Higher levels of ubiquitinated protein were observed in the neointima. Local delivery of potent chemical UBA1 inhibitor PYR-41 (100 μM) and UBA1 shRNA lentivirus both resulted in a substantial decrease in intimal hyperplasia at 2 weeks and 4 weeks after balloon injury. UBA1 inhibition also reduced Ki-67 positive cell percentage and inflammatory response in the carotid artery wall. We further determined that in vitro UBA1 inhibition was able to ameliorate TNF-α-induced nuclear factor-kappa B (NF-κB) activation by reducing IκB degradation in vascular smooth muscle cells (VSMCs). UBA1 inhibition also led to the accumulation of short-lived proteins such as p53, p21 and c-jun, which may account for the UBA1 inhibition-induced cell cycle delay. Thus, VSMCs proliferation was blocked. Conclusions: UBA1 inhibition effectively suppresses neointimal thickening through its anti-proliferative and anti-inflammatory effects. Our results provide further evidence that the ubiquitin-proteasome system is a potential new target for the prevention of vascular restenosis. Highlights: Ubiquitinated proteins were disregulated in neointima of injured carotid arteries. E1 chemical inhibitors or genetically knockdown attenuated neointima formation in injured rat carotid arteries. E1 inhibition reduced monocyte/macrophage infiltration and NF κB activation by blocking IκB degradation. E1 inhibition supressed VSMCs proliferation and chemical inhibitors induced VSMCs apoptosis.